Disturbance of behavior in male secondary school students (Medico Legal Update, 2022)
Background: Behavioral disturbance is a common problem for teenagers all over the world.The prevalence of behavioral disturbance depends on age, family environment, schoolenvironment, and friend relationships.The aim of the study to determine the prevalence ofbehavioral disturbance patterns among male students from age 13-19 yrs. In public secondaryschools in Baghdad, Iraq.Methods: Cross-sectional study done in public secondary schoolsin Baghdad for educational year 2020 - 2021.The sample was collected by multistage clustersampling from 6 schools .Data collection was done through self-administered questionnairefrom 7th February 2021 to 16th march 2021. The questionnaire is comprised of two parts;part 1 was made of demographic characteristics and behavioral disturbance manifestations.Part 2 comprised of socioeconomic characteristics. Results: 600 students were participated inthis study the mean age 15.51.3 . Substance use disorder (15.8%) and bullying (13.5%) werethe common forms of behavioral disturbance. Conclusion: high rates of all behavioraldisturbance were noticed among secondary school students including bullying, substance usedisorder, Rebellion and pornography.